Description of a new bathyal species of Notocomplana (Platyhelminthes, Polycladida) collected from Bathymodiolus aggregations in a deep-sea hydrocarbon seep - Oya, Yuki; Hookabe, Natsumi; Jimi, Naoto; Furushima, Yasuo; Fujiwara, Yoshihiro (Zootaxa, 2025)
Polyclad flatworms are free-living platyhelminths that inhabit various marine environments; however, their biodiversity in the deep sea remains poorly understood. Herein, we describe a new species of Notocomplana Faubel, 1983, Notocomplana profunda sp. nov., based on specimens collected from Bathymodiolus mussel aggregations in a deep-sea hydrocarbon seep off Hatsushima, Japan. This is the first report of a bathyal species of Notocomplana, which is dominated by shallow-water species. The new species is characterized by the absence of tentacles, eyespots, and any color pattern on the dorsal surface of the body and the presence of a seminal vesicle larger than a prostatic vesicle and a long, tubular Lang’s vesicle. A molecular phylogenetic analysis based on the partial sequences of two mitochondrial and two nuclear genes suggested that the strategy of N. profunda sp. nov. to use mussel aggregations was acquired by its shallow coastal ancestors.